2021
DOI: 10.22207/jpam.15.3.39
|View full text |Cite
|
Sign up to set email alerts
|

https://microbiologyjournal.org/in-vitro-evaluation-of-chitosan-hydroxyapatite-nanocomposite-scaffolds-as-bone-substitutes-with-antibiofilm-properties/

Abstract: An opaque, white chitosan/ Hydroxyapatite nanocomposite was prepared by a simple blend method. Morphology, pore size and dispersion of nano-hydroxyapatite in chitosan matrix were visualized using SEM images. The FTIR and SEM with EDX analysis confirmed the bony apatite layer was formed on the outside of the composite. Porosity measurements and water uptake studies of the nanocomposite were evaluated which revealed the maximum porosity of 80% to 92% in the chitosan: hydroxyapatite nanocomposite at the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In addition, in accordance with the studies conducted by A.N. Lipton and co-workers, good antimicrobial activity was obtained for chitosan–hydroxyapatite nanocomposite scaffolds [ 12 ]. In the study entitled “Bioactivity, in vitro corrosion behavior, and antibacterial activity of silver-zeolites doped hydroxyapatite coating on magnesium alloy” H.R.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, in accordance with the studies conducted by A.N. Lipton and co-workers, good antimicrobial activity was obtained for chitosan–hydroxyapatite nanocomposite scaffolds [ 12 ]. In the study entitled “Bioactivity, in vitro corrosion behavior, and antibacterial activity of silver-zeolites doped hydroxyapatite coating on magnesium alloy” H.R.…”
Section: Introductionsupporting
confidence: 85%
“…Chitosan is a natural polysaccharide with unique biological features such as biocompatibility, antimicrobial activity, and so on [ 12 , 14 ]. Titanium (Ti) is often used for biomedical applications (dentistry and orthopedics) and engineering [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The endothermic peak of the HA DSC thermogram occurred at approximately 60 • C, perhaps as a result of moisture loss, while the endothermic peak occurred at approximately 270 • C, which was likely a result of HA degradation. As the melting point of HA is around 1100 • C, it was not captured in DSC [41]. At the same temperature range, the DSC of drug-excipient showed that the primary peaks of the RIS and excipients were evident, and there was no interaction between them.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 98%
“…HAp-chitosan composites have antibacterial activity, both on gram-negative bacteria. Positive and negative bacteria due to the active ingredient chitosan and being able to increase the effectiveness of HAp in binding bioactivity [15].…”
Section: Introductionmentioning
confidence: 99%